Evaluating the prognostic value of cuproptosis-related genes and characterizing PDE3B’s role in gastric cancer: integrative bioinformatics analysis and experimental validation - Chen, Linhui; Wang, Zi; Guo, Yanjun; Li, Chenyang; Zhang, Guoxin (Journal of Gastrointestinal Oncology; Vol 17, No 3 (June 29, 2026): Journal of Gastrointestinal Oncology, 2026)
Background: The identification of cuproptosis offers novel insights into therapeutic strategies for neoplastic diseases. We explore whether cuproptosis and cuproptosis-related genes (CRGs) could provide novel perspectives for the prognosis and treatment of gastric cancer patients.Methods: RNA sequencing data of gastric cancer patients were retrieved from The Cancer Genome Atlas Program (TCGA), CRGs in gastric cancer were analyzed through bioinformatics methods. Subsequent experiments, including Western blotting (WB), quantitative real-time polymerase chain reaction (qRT-PCR), immunofluorescence, 5-Ethynyl-2’-deoxyuridine assay, Cell Counting Kit-8 assay, Transwell assay, transmission electron microscopy, and xenograft tumor formation in nude mice, were conducted to further validate the biological role of the key CRG PDE3B in gastric cancer.Results: We confirmed CP, MAP2K2, and PDE3B as key genes for the prognostic classifier. Knockdown of PDE3B effectively suppressed the pro-tumorigenic functions in gastric cancer cell malignant proliferation and progression. Elesclomol-CuCl2 (ES-Cu) triggered canonical cuproptosis features in gastric cancer cells, and PDE3B expression was downregulated during this process. Notably, the inhibition of PDE3B significantly potentiated ES-Cu induced cuproptosis.Conclusions: We characterized the landscape of CRG dysregulation in gastric cancer, verified that ES-Cu exhibited a significant cytotoxic effect on gastric cancer, and elucidated the pivotal role of PDE3B in gastric cancer.